Using a combined temporal approach to evaluate the influence of ethanol concentration on liking and sensory attributes of lager beer - Ramsey, Imogen; Ross, Carolyn; Ford, Rebecca; Fisk, Ian; Yang, Qian; Gomez-Lopez, Javier; Hort, Joanne (Elsevier, 2018)
A low alcohol beer evoking similar sensory enjoyment as its higher alcohol counterpart is potentially an attractive proposition to breweries for increased sales volumes, as well as consumers due to health and societal reasons. This study aimed to determine the influence of ethanol on the temporal sensory characteristics and liking of beer as perceived by beer consumers. A commercial 0% ethanol concentration lager was spiked with ethanol to different concentrations (0.5%, 2.8%, 5% ethanol). Consumers (n = 101) indicated their liking using temporal liking (TL) methodology (rated throughout consumption) and overall liking (rated at the end of consumption). Consumers also denoted the sensory properties perceived using temporal Check-All-That-Apply (TCATA). Overall, liking data divided consumers into 3 clusters with different patterns of liking. As ethanol concentration increased from 0 to 5%, the TL time that best predicted overall liking shifted from 60 s to 10–20 s indicating that liking of higher alcohol products was decided earlier on in consumption. Data suggested that in a lower ethanol beer, a liking judgement may not be stabilized until later in the evaluation, while in high ethanol beers, a liking judgement, either positive or negative, stabilised more rapidly. TCATA results revealed different temporal sensory profiles among the different ethanol concentrations. As ethanol concentration increased, the citation of sweetness, fullness/body and alcohol warming sensation increased. However, the relationship between TCATA citations and TL varied among the three clusters highlighting that, in relation to ethanol concentration, different negative and positive sensory drivers of preference exist for different segments of consumers.